The interaction of sexual orientation and provider-patient communication on sexual and reproductive health in a sample of U.S. women of diverse sexual orientations. Issue 2 (February 2022) - Tabaac, Ariella R.; Sutter, Megan E.; Haneuse, Sebastien; Agénor, Madina; Bryn Austin, S.; Guss, Carly E.; Charlton, Brittany M.
Highlights: Provider-patient communication may improve contraceptive use for sexual minority women. Referral can improve sexually transmitted infection testing among all women. Lesbians need to receive more communication about sexual and reproductive health. Abstract: Objective: Our goal was to examine associations among provider-patient communication, past-year contraceptive use and lifetime sexually transmitted infection. Methods: Data were analyzed cross-sectionally from 22, 554 women in the Growing Up Today Study and Nurses' Health Study 3 between the follow-up period of 1996–2020. We used multivariable Poisson regression models adjusted for race/ethnicity, age in years, study cohort, and region of residence to obtain risk ratio (RR) associations and 95% confidence intervals (CI). Results: Provider-patient communication was associated with higher likelihood of using all methods of past-year contraceptive use (RRs ranging from 1.11 to 1.63) and lifetime STI diagnosis (RRs ranging from 1.18 to 1.96). Completely heterosexual women with no same-sex partners (referent) were 13% more likely than lesbians and 4% less likely than other groups to report a provider ever discussed their SRH. Significant interactions emerged between sexual minority status and provider-patient communication. Sexual minority women whose providers discussed their SRH were less likely to report contraceptive non-use in the past year ( p  < .0001). Conclusion: Provider-patient communication may benefit sexual minority women's contraceptive practices and engagement with STI testing. Practice implications: Differences in provider-patient SRH discussion by sexual orientation indicate lesbian women are not receiving the same attention in clinical encounters.